Associations between prenatal maternal exposure to per- and polyfluoroalkyl substances (PFAS) and polybrominated diphenyl ethers (PBDEs) and birth outcomes among pregnant women in San Francisco - Stephanie M. Eick; Elizabeth K. Hom Thepaksorn; Monika A. Izano; Lara J. Cushing; Yunzhu Wang; Sabrina Crispo Smith; Songmei Gao; June-Soo Park; Amy M. Padula; Erin DeMicco; Linda Valeri; Tracey J. Woodruff; et al. (BMC, 2020)
Abstract Background Perfluoroalkyl substances (PFAS) and polybrominated diphenyl ethers (PBDEs) are used in consumer products for their water repellent and flame retardant properties, respectively. However, there is widespread prenatal exposure and concern about their potential harm to the developing fetus. Here, we utilized data from a demographically diverse cohort of women in San Francisco, CA to examine associations between prenatal exposure to PFAS and PBDEs with gestational age and birth weight for gestational age z-scores. Methods Women included in this analysis were enrolled in the Chemicals in our Bodies (CIOB) cohort study (N = 506). PFAS and PBDEs were measured in serum obtained during the second trimester of pregnancy. Linear regression models were used to calculate crude and adjusted β coefficients for the association between PFAS and PBDE concentrations in tertiles and gestational age and birth weight z-scores. Individual PFAS and PBDE concentrations, as well as their sums, were examined in separate models. Results The highest compared to lowest tertile of BDE-47 was associated with shorter gestational age (β = − 0.49, 95% confidence interval [CI] = − 0.95, − 0.02). Additionally, exposure to BDE-47 and BDE-99 in the middle tertile was also associated with a reduction in birth weight z-scores (β = − 0.26, 95% CI = -0.48, − 0.04; β = − 0.25, 95% CI = -0.47, − 0.04, respectively) compared to those in the lowest tertile of exposure. No consistent associations were observed between increasing PFAS concentrations and gestational age or birth weight z-scores. Discussion Among a diverse group of pregnant women in the San Francisco Bay Area, we found non-linear associations between prenatal exposure to PBDEs during the second trimester of pregnancy and birth weight z-scores. However, most PFAS congeners were not associated with adverse birth outcomes. PFAS and PBDE concentrations were lower in our cohort relative to other studies. Future research should assess the effects of emerging and persistent PFAS and PBDEs on birth outcomes, as some congeners are being phased out and replaced by chemically similar structures.